Interstitial fibrosis and arrhythmic mitral valve prolapse: Unraveling sex-based differences - Lionel Tastet; Shalini Dixit; Rohit Jhawar; Thuy Nguyen; Mohammad Al-Akchar; Dwight Bibby; Farzin Arya; Luca Cristin; Shafkat Anwar; Satoshi Higuchi; Henry Hsia; Yoo Jin Lee; et al. (Journal of Cardiovascular Magnetic Resonance)
ABSTRACT: Background: Interstitial fibrosis as quantified by cardiovascular magnetic resonance (CMR) has been demonstrated in arrhythmic mitral valve prolapse (AMVP), a condition with known female predominance. Prior studies of interstitial fibrosis in AMVP have only included cases with significant mitral regurgitation (MR) or mitral annular disjunction (MAD), limiting our understanding of alternative arrhythmic mechanisms in mitral valve prolapse (MVP). We sought to evaluate the association between interstitial fibrosis and AMVP, regardless of MAD and without severe MR, while also investigating the contribution of sex to this association. Methods: We performed research-based contrast CMR in consecutive individuals with MVP between 2019 and 2022. Extracellular volume fraction (ECV%), a surrogate marker for interstitial fibrosis, was quantified using T1 mapping in the basal and mid-left ventricular slices. Replacement fibrosis was assessed using late gadolinium enhancement (LGE). AMVP was defined as MVP with frequent premature ventricular contractions and/or non-sustained/sustained ventricular tachycardia (VT) or fibrillation (VF). Results: We identified 65 MVP cases without severe MR (30 [46%] women, 22 [34%] no/trace, 30 [44%] mild, and 13 [21%] moderate MR) and with adequate ECV% measurement. Among these, 38% were classified as AMVP, including two cases of aborted VF arrest, both in premenopausal females. Global ECV% was significantly higher in AMVP vs non-AMVP (31% [27-33] vs 27% [23-30], p = 0.002). In the AMVP group, higher segmental ECV% was not limited to the inferolateral/inferior walls, typically subject to myocardial traction by the prolapsing leaflets/MAD but was more diffuse and involved atypical segments such as the anterior/anterolateral walls (p < 0.05). The association between AMVP and global ECV% was driven by female sex (32% [30-34] vs 27% [25-30], p = 0.002 in females; 28% [23-32] vs 26% [23-30], p = 0.41 in males). ECV% remained independently associated with an increased risk of arrhythmic events, including VT/VF (p < 0.01), even after adjustment for cardiovascular risk factors, MAD, and LGE (p < 0.01). Conclusion: In MVP without significant MR, interstitial fibrosis by CMR is associated with an increased risk of arrhythmic events, suggesting a primary myopathic process. The selective association between interstitial fibrosis and AMVP in females may explain why severe arrhythmic complications are more prevalent among women.